Analysis of Occupational Safety Risk Management in Crane Based Well Services Activities in Budi Field Oil Field - Yesiawan ADI; Edi SETIAWAN; Soehatman RAMLI (PT Keberlanjutan Strategis Indonesia, 2026)
Crane Based Well Services (CBWS) is a new technology in oil well maintenance in the oil and gas world. Tately N.V. is one of the marginal oil and gas companies, has implemented several CBWS campaigns in their oil wells. This study examines how the analysis and management of occupational safety risks arising from these activities. In CBWS activities, there are several potential hazards in the stages of its activities, including the danger of gas coming out of the well, the danger of wild sprays, the danger of lifting tools failure, the danger of working at heights, the danger of high pressure release, the danger of pinch points, the danger of irregular material swings and the danger of crane legs collapsing. Activities with these potential hazards have a high to moderate risk of causing work accidents. To reduce the risk of accidents from CBWS activities, Tately N.V. has taken mitigation measures for each potential hazard identified. The results of the study showed that the mitigation measures were quite successful with a decrease in the risk assessment to light, so that activities can be carried out with the mitigation that has been carried out. This study shows that much simpler and more economical CBWS activities can be carried out safely and with zero accidents by implementing the recommended mitigation or prevention measures to reduce existing K3 risks.